Bijak Mengetik, Sopan Santun Dalam Berucap: Etika Komunikasi Pelajar Yang Bebas Bullying Di SMA Negeri 1 Cepogo - Hafsah Syahidah; Galuh Wahyu Lestari; Galih Wahyu Agista; Hamdan Ramadhan Amirul Ihsan; Nurul Hidayati (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aims to help students better understand communication ethics and reduce the risk of bullying and cyberbullying through a socialization program titled “Typing Wisely, Speaking Politely: Communication Ethics for a Bullying-Free Student Environment at SMA Negeri 1 Cepogo.” The rationale behind this activity is the students’ improper use of digital media and their tendency to communicate disrespectfully such as mocking others, sharing photos without permission, and excessive joking which can lead to bullying. The method used is a combination of qualitative descriptive data and quantitative data from pre-test and post-test results. The activity involved delivering material, interactive discussions, case simulations, short interviews, and comprehension evaluations. The results showed a significant improvement in students' understanding, as indicated by the pre-test score of 80% increasing to 100% in the post-test. Students also demonstrated behavioral changes, such as becoming more aware of the limits of joking, respecting privacy, and understanding the legal risks of digital communication. This activity shows that school-based education can be an effective way to build a culture of ethical, empathetic, and bullying-free communication. These findings highlight the importance of continuous digital literacy programs to foster a safe and harmonious school environment.